Hardwired… to Self-Destruct? Using Technology to Improve Behavior Change Science. Issue 1 (21st May 2021) - Crutzen, Rik
Many societal problems are related to human behavior. To change behavior, it is crucial to be aware of Lewin's formula indicating that behavior is a function of a person and their environment. Technology provides opportunities with regard to (measurement of) all three elements of this formula. This raises the question how existing technologies can be used to improve behavior change science. This article provides two answers to this question: application and innovation of theory. Technology can be used to apply behavior change methods in practice. For example, providing computer-tailored feedback based on a social-cognitive profile. Technology can also be used to innovate theory, which is less common, but results in more progress. For example, technology provides opportunities to triangulate ecological momentary assessment (EMA) with smartphone native sensor data to track behavior and environmental factors. If the opportunities provided by technology are combined with a rationale on how and which data to collect, then these data can be used to answer theoretically driven questions. Answering such questions results in better theories to both explain and change behavior. This is highly relevant for more effective and more efficient solutions to all societal problems related to human behavior.